Peningkatan Produktivitas Melalui Pelatihan Karyawan Pada PT. Giordano Indonesia - Firstianty Wahyuhening Fibriany (Cakrawala - Jurnal Humaniora, 2017)
The development and advancement of an organization cannot be separated from the factor of quality human resources owned by that company. Productivity can reflect the success or failure in achieving effectiveness and efficiency in the use of company resources. Good work productivity can not be obtained by reversing the Palm of the hand, but should be done with hard work, both in the short term, or long term. One way that's done the company to improve productivity and performance is to conduct training to employees, especially new employees who recently was hired by the company in order to reduce the gap between the ability of employees with the skills that are required of the company.Keywords:  Employee, Productivity, Employee Training